1998
DOI: 10.1038/sj.leu.2401102
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of c-kit receptor and response to stem cell factor in childhood malignant T-lymphoblastic cells

Abstract: The cytokine stem cell factor (SCF) synergizes with IL-7 to enhance the proliferation of thymocytes. We therefore investigated the role of the SCF receptor, the protooncogene c-kit, in the pathogenesis of pediatric T-lineage malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Bcl-6 expression is less often observed in T-LBL with a DN phenotype [26], while CD117 is known to play a role in early thymocyte (DN stage) development [27]. CD117 expression was reported in up to 40% of patients with T-ALL/LBL [28], and is more commonly seen in cases with the most immature phenotypes [29]. Expression of CD13, a non-Trestricted marker, is often observed in CD117+ TLBLs [29], probably reflecting a prethymic precursor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-6 expression is less often observed in T-LBL with a DN phenotype [26], while CD117 is known to play a role in early thymocyte (DN stage) development [27]. CD117 expression was reported in up to 40% of patients with T-ALL/LBL [28], and is more commonly seen in cases with the most immature phenotypes [29]. Expression of CD13, a non-Trestricted marker, is often observed in CD117+ TLBLs [29], probably reflecting a prethymic precursor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Kit is upregulated by BMP4 in mitotic spermatogonia It has been shown that TGF-β can downregulate c-kit expression in hemopoietic cells (Sansilvestri et al, 1995;Heinrich et al, 1995), while it upregulates c-kit expression in T-leukemia cells and in melanoblasts (Tomeczkowski et al, 1998;Kawakami et al, 2002). To date no reports have been obtained on the factors that regulate c-kit expression in germ cells.…”
Section: Smad4/5 and Cbp Form An Active Complex Upon Bmp4 Stimulationmentioning
confidence: 99%
“…Mutations of the receptor tyrosine kinase and oncogene c-KIT have been identified as a common event in some cases of AML and T-cell ALL (Goemans et al, 2005;Shih et al, 2008;Tomeczkowski et al, 1998). One study has shown in vitro that KIT exon 8 mutations transiently expressed in CHO cell line can result gain of function in constitutively activating a ligand-independent KIT kinase via autophosphorylation (Goemans et al, 2005).…”
Section: Supporting Publications 2016: En-955 113mentioning
confidence: 99%